The Investigation of Reducing PAHs Emission from Coal Pyrolysis by Gaseous Catalytic Cracking - Yulong Wang; Ruifang Zhao; Chun Zhang; Guanlong Li; Jing Zhang; Fan Li (The Scientific World Journal)
The catalytic cracking method of PAHs for the pyrolysis gaseous products is proposed to control their pollution to the environment. In this study, the Py-GC-MS is used to investigate in situ the catalytic effect of CaO and Fe2O3 on the 16 PAHs from Pingshuo coal pyrolysis under different catalytic temperatures and catalyst particle sizes. The results demonstrate that Fe2O3 is effective than that of CaO for catalytic cracking of 16 PAHs and that their catalytic temperature corresponding to the maximum PAHs cracking rates is different. The PAHs cracking rate is up to 60.59% for Fe2O3 at 600°C and is 52.88% at 700°C for CaO. The catalytic temperature and particle size of the catalysts have a significant effect on PAHs cracking rate and CaO will lose the capability of decreasing 16 PAHs when the temperature is higher than 900°C. The possible cracking process of 16 PAHs is deduced by elaborately analyzing the cracking effect of the two catalysts on 16 different species of PAHs.